Intervenciones de enfermería relacionada con el control del crecimiento y desarrollo en niños menores de cinco años con desnutrición crónica, cantón Montalvo octubre 2018 – abril 2019 - Sanchez Meza, Melissa Aydee (2019)
Introduction. Nursing interventions in the control of growth and development of the child, is one of the most important activities that must be fulfilled by the health professional, in each of the levels of care. General objective. To determine the interventions applied by nurses in the control of growth and development in children under five years of age with chronic malnutrition in the Montalvo Subcenter of Health of Los Ríos province in the period from October 2018 to April 2019. Methodology. Qualitative-quantitative field research, exploratory and descriptive, applied and non-experimental, cross-sectional. Information gathering techniques were used as unscientific scientific observation, direct and survey; A questionnaire was applied as an instrument. The universe and the sample of 33 children respectively, sampling was intentional non-probabilistic. Results. Age group of 3 to 5 years (54.6%), mixed lactation (81.4%), with anemia (54.5%) and food intolerance (51.5%), mothers over 35 years (54, 6%), with anemia (69.7%), and primary education (39.3%), living in families with low economic status (63.7%), children of divorced parents in 60.7%, mothers with 4 children (48.4%). Nursing graduates (60%) who do not do the evaluation (54.6%), do not use clear language when explaining to mothers about caring for their children (57.6%), do not formulate diagnoses (75.8%), do not plan activities (54.6%). Conclusions. Mixed breastfeeding, anemia, food intolerance, advanced age, anemia in mothers, low level of education and socioeconomic status, family instability due to parental divorce and number of children over four were identified as the main factors. They stop applying interventions to control the growth and development of children under five years of age with chronic malnutrition.